2012
DOI: 10.3109/17435390.2012.744110
|View full text |Cite
|
Sign up to set email alerts
|

IL-1R signalling is critical for regulation of multi-walled carbon nanotubes-induced acute lung inflammation in C57Bl/6 mice

Abstract: Exposure to certain engineered nanomaterials has been associated with pathological changes in animal models raising concerns about potential human health effects. MWCNT have been reported to activate the NLRP3 inflammasome in vitro, correlating with lung inflammation and pathology, in vivo. In this study, we investigated the role of IL-1 signalling in pulmonary inflammatory responses in WT and IL-1R−/− mice after exposure to MWCNT. The results suggest that MWCNT were effective in inducing acute pulmonary infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 53 publications
1
50
1
Order By: Relevance
“…apoptosis [13,22,34,43,60]. An indirect but crucial role for IL-1 in the pathogenicity of CNTs has been demonstrated in C57BL/6 mice lacking IL-1 receptor (IL-1R À/À ) [14]. The results demonstrated that CNT exposure induced IL-1b production within 24 h accompanied with an acute inflammatory response which was absent in IL-1R À/À mice 24 h post CNT exposure [14].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…apoptosis [13,22,34,43,60]. An indirect but crucial role for IL-1 in the pathogenicity of CNTs has been demonstrated in C57BL/6 mice lacking IL-1 receptor (IL-1R À/À ) [14]. The results demonstrated that CNT exposure induced IL-1b production within 24 h accompanied with an acute inflammatory response which was absent in IL-1R À/À mice 24 h post CNT exposure [14].…”
Section: Introductionmentioning
confidence: 84%
“…The various members, including IL-1a and IL-1b, play a role in the cellular responses induced by exposure to nanoparticles [34,43]. IL-1a, which is active in both its precursor form and mature form, and IL-1b which is encoded as a pro-IL-1b protein and then processed by caspase-1 into a mature IL-1b protein [5,16], are regulated in response to a variety of nanoparticles in vitro and in vivo [9,14,31,33,37,61,62]. Nanoparticles induce expression of IL-1a and IL-1b in lipopolysaccharide (LPS)-primed macrophages [36], of IL-1b in human monocytes [31], fibroblasts in vitro [47], and in vivo inflammasome-associated IL-1b has been implicated in the pathogenicity of carbon nanotube (CNT) nanoparticles [18,48].…”
Section: Introductionmentioning
confidence: 99%
“…CNTs have been previously associated with foreign body reactions, 21,23 including migration, activation of immune cells and induction of frustrated phagocytosis, 25 and activation of the NLRP3 inflammasome, 3,[27][28][29][30]41 leading to inflammation. 60 The nanometer scale and needle shape of CNTs recall that of crocidolite asbestos fibers, 54 and CNT administration has been associated with inflammation, fibrosis, and mesothelioma.…”
Section: Discussionmentioning
confidence: 99%
“…14,[20][21][22][23] The effects of pristine (nonfunctionalized) CNTs most commonly involve immune innate reactions, including enhancement of oxidative damage, 24 fibrosis, 13,22,23 collagen-rich granuloma formation, 23 and inflammation. [25][26][27][28][29][30] When entering biological fluids, CNTs are rapidly coated by proteins, forming a biological protein corona. 31,32 In particular, the hydrophobic interactions between CNTs and proteins could also play a role in inducing proteins to form a cross-sheet, a characteristic of amyloid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation